Вы находитесь на странице: 1из 6

Examples of Proof by Contradiction

Example 1: Prove the following statement by Contradiction.


There is no greatest even integer.
Proof:
Suppose not. [We take the negation of the theorem and suppose it to be true.] Suppose there is greatest
even integer N. [We must deduce a contradiction.] Then
For every even integer n, N ≥ n.
Now suppose M = N + 2. Then, M is an even integer. [Because it is a sum of even integers.] Also, M > N
[since M = N + 2]. Therefore, M is an integer that is greater than the greatest integer. This contradicts the
supposition that N ≥ n for every even integer n. [Hence, the supposition is false and the statement is true.]
And this completes the proof.

Example 2: Prove the following statement by Contradiction.


The difference of any rational number and any irrational number is irrational.
Proof:
Suppose not. [We take the negation of the theorem and suppose it to be true.] Suppose ∃ a rational number
x and an irrational number y such that (x − y) is rational. [We must derive a contradiction.] By definition of
rational, we have
x = a/b for some integers a and b with b ≠ 0.
and x − y = c/d for some integers c and d with d ≠ 0.
By substitution, we have
x − y = c/d
a/b − y = c/d
y = a/b − c/d
= (ad − bc)/bd
But (ad − bc) are integers [because a, b, c, d are all integers and products and differences of integers are
integers], and bd ≠ 0 [by zero product property]. Therefore, by definition of rational, y is rational. This
contradicts the supposition that y is rational. [Hence, the supposition is false and the theorem is true.]
And this completes the proof.

Example 3: Prove the following statement by contradiction:


The negative of any irrational number is irrational.
First, translate given statement from informal to formal language:
∀ real numbers x, if x is irrational, then −x is irrational.
Proof:
Suppose not. [we take the negation of the given statement and suppose it to be true.] Assume, to the
contrary, that
∃ irrational number x such that −x is rational.
[We must deduce the contradiction.] By definition of rational, we have
−x = a/b for some integers a and b with b ≠ 0.
Multiply both sides by −1, gives
x = −(a/b)
= −a/b
But −a and b are integers [since a and b are integers] and b ≠ 0 [by zero product property.] Thus, x is a ratio
of the two integers −a and b with b ≠ 0. Hence, by definition of ration x is rational, which is a
contradiction. [This contradiction shows that the supposition is false and so the given statement is true.]
This completes the proof.

HP Page 1
Example 4: Prove the following statement by contradiction:
For all integers n, if n2 is odd, then n is odd.
Proof:
Suppose not. [We take the negation of the given statement and suppose it to be true.] Assume, to the
contrary, that ∃ an integer n such that n2 is odd and n is even. [We must deduce the contradiction.] By
definition of even, we have
n = 2k for some integer k.
So, by substitution we have
n . n = (2k) . (2k)
= 2 (2.k.k)
Now (2.k.k) is an integer because products of integers are integer; and 2 and k are integers. Hence,
n . n = 2 . (some integer)
or n2 = 2. (some integer)
and so by definition of n2 even, is even.
So the conclusion is since n is even, n2, which is the product of n with itself, is also even. This contradicts
the supposition that n2 is odd. [Hence, the supposition is false and the proposition is true.]

Examples of Direct Method of Proof

Example 1 (Version I): Prove the following universal statement:


The negative of any even integer is even.
Proof:
Suppose n is any [particular but arbitrarily chosen] even integer. [We must show that −n is even.]
By definition of even number, we have
n = 2k for some integer k.
Multiply both sides by −1, we get
−n = −(2k)
= 2. (−k)
Now let r = -k. Then r is an integer [because a product of two integers is an integer],
r = −k
= (−1) k [and −1 and k are integers.]
Hence,
−n = 2r for some integer r.
And so by definition of even number, −n is even. This what was to be shown.
And this completes the proof.

Example 1 (Version II): Prove the following universal statement:


The negative of any even integer is even.
Proof:
Suppose n is any even integer. By definition of even number,
n = 2k for some integer k
Then,
−n = −2k
= 2 (−k)
But, by definition of even number, 2(−k) is even [because -k is an integer (being the product of the integers
−1 and k).]

HP Page 2
Hence, −n is even. This is what was to be shown.
And this completes the proof.

Example 2: Prove the following universal statement:


If n is any even integer, then (−1)n = 1.
Proof:
Suppose n is even [particular but arbitrarily chosen] integer. [We must show that (−1)n = 1.]. Then by the
definition of even numbers,
n = 2k for some integer k
Hence, by the laws of exponents of algebra, we have
(−1)n = (v1)2k
= ((−1)2)k
= (1)k
=1
This is what was to be shown.
And this completes the proof.

Example 3: Prove the following universal statement:


The product of any two odd integers is odd.
Proof:
Suppose m and n are any [particular but arbitrarily chosen] odd integers. [We must show that (m.n) is odd.]
By the definition of odd numbers, we have
n = 2r + 1 for some integer r
m = 2s + 1 for some integer s
Then, by substitution, we have
m . n = (2r + 1) . (2s + 1)
= 4rs + 2r + 2s + 1
= 2(2rs + r + s) + 1
Now, (2rs + r + s) is an integer [because products and sums of integers are integers and 2, r and s are all
integers] and therefore, by definition of odd number, (m.n) is odd. This is what was to be shown.
And this completes the proof.

Example 4: Prove the following universal statement:


For all integers n, 4(n2 + n + 1) − 3n2 is a perfect square.
Proof:
Let n is any [particular but arbitrarily chosen] integer. [We must show that (4(n2 + n + 1) − 3n2) is a perfect
square.] Then, we have
4(n2 + n + 1) − 3n2 = 4n2 + 4n + 4 − 3n2
= n2 + 4n + 4
= (n + 2)2
But is a perfect square [because (n+2) is an integer (being a sum of n and 2).] Hence, (4(n2 + n + 1) − 3n2)
is an integer, as was to be shown.
And this completes the proof.

HP Page 3
Example 5: Prove the following universal statement:
Every integer is a rational number.
Proof:
Suppose n is any [particular but arbitrarily chosen] integer. [We must show that n is a rational number.]
Then
n=n.1
and so
n = n/1
Now n and 1 are both integers and 1 ≠ 0. Hence, n can be written as a quotient of integers with a nonzero
denominator, and so n is rational.
And this completes the proof.

Example 6: Prove the following universal statement:


The sum of any two rational numbers is rational.
Proof.
Suppose r and s are rational numbers. [We must show that r + s is rational.] Then, by the definition of
rational numbers, we have
r = a/b for some integers a and b with b ≠ 0.
s = c/d for some integers c and d with d ≠ 0.
So, by substitution, we have
r + s = a/b + c/d
= (ad + bc)/bd
Now, let p = ad + bc and q = bd. Then, p and q are integers [because products and sums of integers are
integers and because a, b, c and d are all integers. Also, q ≠ 0 by zero product property.] Hence,
r + s = p/q , where p and q are integers and q ≠ 0.
Therefore, by definition of a rational number, (r + s) is rational. This is what was to be shown.
And this completes the proof.

Example 7: Prove the following universal statement:


The product of any two rational numbers is a rational number.
Proof:
Suppose r and s are rational numbers. [We must show that r.s is rational.] Then, by definition of rational
number, we have
r = a/b for some integers a and b with b ≠ 0.
s = c/d for some integers c and d with d ≠ 0.
So, by substitution, we have
r . s = (a/b) . (c/d)
= (ac)/bd
Now, (ac) and (bd) are both integers (being product of integers) and (bd) ≠ 0 (by the zero product
property). Hence, (r.s) is a quotient of integers with a nonzero denominator, and so by definition of rational
number, (r.s) is rational. This is what was to be shown.
And this complete the proof.

Example 10: Prove the following universal statement:


For all integer a, b and c, if a|b and a|c, then a|(b+c).
Proof:
Suppose a, b and c are any integers such that a|b and a|c. [We must show that a|(b+c).] By definition of
divisibilty, we have
b = a . r for some integer r.

HP Page 4
and c=a.s for some integer s.
Then, by substitution, we have
b+c=a.r+a.s
= a (r + s)
Let t = r + s. Then t is an integer [being a sum of integers], and thus
b + c = a . t for some integer t
Then, by definition of divisibility, a|(b+c) and this is what was to be shown.
And this completes the proof.

Proofs by Principle of Mathematical Induction

Example 1: For any natural number n , 2 + 4 + ... + 2n = n( n + 1 ).

Proof:
Basis Step: If n = 0, then LHS = 0, and RHS = 0 * (0 + 1) = 0 .
Hence LHS = RHS.
Induction:
Assume that for an arbitrary natural number n,
0 + 2 + ... + 2n = n( n + 1 )-Induction Hypothesis

To prove this for n+1, first try to express LHS for n+1 in terms of LHS for n, and somehow use the
induction hypothesis.
Here let us try
LHS for n + 1 = 0 + 2 + ... + 2n + 2(n + 1) = (0 + 2 + ... + 2n) + 2(n + 1) .
Using the induction hypothesis, the last expression can be rewritten as
n( n + 1 ) + 2(n + 1) .
Factoring (n + 1) out, we get
(n + 1)(n + 2) ,
which is equal to the RHS for n+1.

Thus LHS = RHS for n+1.

By Principle of Mathematical induction we can say that 2 + 4 + ... + 2n = n( n + 1 ) is true for any natural
number n.

Example 2:For any natural number n , 12 + 22 + ... + n2 = n( n + 1 )( 2n + 1 )/6.

Proof:
Basis Step: If n = 0, then LHS = 02 = 0, and RHS = 0 * (0 + 1)(2*0 + 1)/6 = 0 .
Hence LHS = RHS.
Induction: Assume that for an arbitrary natural number n,
12 + 22 + ... + n2 = n( n + 1 )( 2n + 1 )/6. -------- Induction Hypothesis

To prove this for n+1, first try to express LHS for n+1 in terms of LHS for n, and use the induction
hypothesis.
Here let us try
LHS for n + 1 = 12 + 22 + ... + n2 + (n + 1)2 = ( 12 + 22 + ... + n2 ) + (n + 1)2
HP Page 5
Using the induction hypothesis, the last expression can be rewritten as
n( n + 1 )( 2n + 1 )/6 + (n + 1)2
Factoring (n + 1)/6 out, we get
( n + 1 )( n( 2n + 1 ) + 6 ( n + 1 ) )/6
= ( n + 1 )( 2n2 + 7n + 6 )/6
= ( n + 1 )( n + 2 )( 2n + 3 )/6 ,
which is equal to the RHS for n+1.

Thus LHS = RHS for n+1.

By Principle of Mathematical induction we can say that 12 + 22 + ... + n2 = n( n + 1 )( 2n + 1 )/6 is true


for any natural number n.

Examples of Contrapositive Proofs

Example 1:For any integers a and b, a+ b ≥ 15 implies that a ≥ 8 or b ≥ 8.

Proof: We’ll prove the contrapositive of this statement.


That is, for any integers a and b, a < 8 and b < 8 implies that a+b < 15.
So, suppose that a and b are integers such that a < 8 and b < 8.
Since they are integers (not e.g. real numbers), this implies that
a ≤ 7 and b ≤ 7. Adding these two equations together, we find
that a + b ≤ 14. But this implies that a + b < 15.

Example 2: Suppose x is an integer. If 7x+19 is even, then x is odd.

Example 3: Suppose x and y are rational numbers. If

HP Page 6